Kesiapsiagaan Masyarakat Terhadap Ancaman Bencana Tsunami di Kota Pariaman - ananda, Livia tri (JURNAL BUANA, 2025)
This study aims to determine 1) the level of tsunami hazard in Pariaman City, 2) the level of community preparedness against the threat of a tsunami disaster in Pariaman City. The research method used in this research is descriptive quantitative research method. Based on the results of the study, the results obtained: 1) the level of tsunami vulnerability in Pariaman City is divided into 3 classes, namely high class 17.66%, medium class 71.64% and low class 10.70% of the area, 2) City community preparedness level Pariaman to tsunamis at high tsunami levels is in the very ready category at 79.5%, at the medium tsunami level in the ready category at 76.2%, and at low tsunami levels in the ready category at 70.1%.